2019
DOI: 10.1093/cvr/cvz152
|View full text |Cite
|
Sign up to set email alerts
|

TXNIP/Redd1 signalling and excessive autophagy: a novel mechanism of myocardial ischaemia/reperfusion injury in mice

Abstract: Aims Either insufficient or excessive autophagy causes cellular death and contributes to myocardial ischaemia/reperfusion (I/R) injury. However, mechanisms controlling the ‘right-level’ of autophagy in the heart remains unidentified. Thioredoxin-interacting protein (TXNIP) is a pro-oxidative molecule knowing to contribute to I/R injury. However, whether and how TXNIP may further inhibit suppressed autophagy or promote excessive cardiac autophagy in I/R heart has not been previously investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 35 publications
0
70
0
Order By: Relevance
“…Indeed, in recent years, there have been increasing numbers of studies unveiling new information on autophagy. Emerging evidence has revealed that autophagy may also promote cell death through excessive autophagosomes formation, which can be obtained from recent papers (Wang et al, 2015;Gao et al, 2018;Gao et al, 2019). These groups demonstrate that inhibition of redundant autophagosomes effectively protects cardiomyocytes from ischemic injury.…”
Section: Ubc9 and Autophagic Flux Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in recent years, there have been increasing numbers of studies unveiling new information on autophagy. Emerging evidence has revealed that autophagy may also promote cell death through excessive autophagosomes formation, which can be obtained from recent papers (Wang et al, 2015;Gao et al, 2018;Gao et al, 2019). These groups demonstrate that inhibition of redundant autophagosomes effectively protects cardiomyocytes from ischemic injury.…”
Section: Ubc9 and Autophagic Flux Regulationmentioning
confidence: 99%
“…The apoptotic cardiomyocytes were stained with TUNEL dye (Gao et al, 2019). Procedures are described in Supplementary data.…”
Section: Tunel Stainingmentioning
confidence: 99%
“…Although the role of autophagy in oxidative stress has been widely examined in recent years, few studies have specifically addressed the role of end-stage autophagy, and those that have, yielded controversial results [7,8]. For instance, ROS were found to inhibit the clearance of autophagic lysosomes at the end of the ischemia-reperfusion period, thus promoting the occurrence of cell apoptosis and aggravating cell damage [9], while other studies have suggested that promoting autophagy can reduce the inflammatory response caused by mitochondrial damage [10]. Recently, a new type of programmed cell death, pyroptosis has been described, which consists of focal cell death primarily occurring through recognition of pathogen-associated molecular patterns (PAMPs) and danger-associated molecular patterns (DAMPs), which activates the immune cell receptor and promotes the expression of NOD-like receptor family, pyrin domain containing 3 (NLRP3), caspase 1, and interleukin-(IL-) 1β, as well as other inflammatory factors [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…During reperfusion, a large amount of inflammatory factors is produced to promote tissue infiltration of inflammatory cells, thus affecting cell structures and functions ( 11 ). Hypoxia/reoxygenation (H/R) in cells is a major characteristic of I/R, and is frequently used to simulate the activity of I/R ( 12 , 13 ). Low cell viability, high apoptosis and inflammatory responses occur after cell injury induced by H/R ( 14 ).…”
Section: Introductionmentioning
confidence: 99%